PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIKA SISWA - Noviyana, Hesti (JURNAL e-DuMath, 2017)
Abstract: The problems in this study relate to the learning model of Project Based Learning and students creative thinking ability in mathematics. The purpose of the research to know the influence of the model of Project Based Learning on the ability to think creatively mathematics students VIII grade even semester SMP Negeri 3 Bandar Lampung lesson 2016/2017 . The research used experimental method with the population that is all students of class VIII with the amount of 347, while the sample is taken 2 class that is class VIII A as experiment class which amounted to 31, class VIII C as control class which amounted 30. The sample was taken using Cluster Random Sampling technique. To know the ability of creative thinking mathematics students authors perform tests in the form of essays as many as 5 questions that have been tested the validity and reliability. Hypothesis testing in this study using t test. From the results of hypothesis testing using t-test obtained t value = 14.27. From the distribution table t at the significant level of 5% is known t = 2.00 means t> t, so it can be concluded